A Typology of Syekh Yusuf Al-Makassari's Ethical Thought (Perspective of Majid Fakhry's Islamic Ethics Theory) - Muh. Bahrul Afif; Abdul Malik; Abd. Rahman (Journal Analytica Islamica, 2024)
Deep reflection on the teachings and moral views in the Quran and Hadith has been done by many Islamic scholars and thinkers. From this reflective activity, they produce concepts of Islamic ethics with various typologies depending on the style of thinking. Fakhry through his research classified the typology of Islamic ethics in four categories: scriptural morality; theological ethics; philosophical ethics; and religious ethics, and established each of their exponents. However, the scope of his study is still limited to the Arab-Persian region and its figures who lived up to XIII century. This research seeks to go beyond that by focusing on Syekh Yusuf al-Makassari-a major Nusantara figure who lived in the XVII century-and determining the typology of his ethical thought. By utilising Fakhry's view on the typology of Islamic ethics as the theoretical basis, the results of this study demonstrate that Syekh Yusuf's ethical thinking belongs to the typology of religious ethics. This is because it contains various aspects that are the main components of religious ethics, namely aspects of the Quran and Hadith, theology, philosophy, and Sufism.